Thyroid autoimmunity and its negative impact on female fertility and maternal pregnancy outcomes - Tańska, Kamila; Gietka-Czernel, Małgorzata; Glinicki, Piotr; Kozakowski, Jarosław (Frontiers in Endocrinology, 2023)
Thyroid autoimmunity (TAI) is commonly defined as the presence of thyroperoxidase antibodies (TPOAbs), and/or thyroglobulin antibodies (TgAbs), which predisposes to hypothyroidism. TAI affects nearly 10 percent of women of reproductive age and evokes great interest from clinicians because of its potentially negative impact on female fertility and pregnancy course. In this mini-review, we review the current literature concerning the influence of TPOAb or TPOAb/TgAb positivity without thyroid dysfunction on reproduction. TAI may negatively affect female fertility; several studies have found an increased prevalence of TAI in infertile women, especially in those with unexplained infertility and polycystic ovary syndrome. According to some observations, TAI might also be connected with premature ovarian insufficiency and endometriosis. The relationship between TAI and an increased risk of pregnancy loss is well documented. The pathophysiological background of these observations remains unclear, and researchers hypothesize on direct infiltration of reproductive organs by thyroid antibodies, co-existence of TAI with other autoimmune diseases (either organ-specific or systemic), immunological dysfunction leading to inhibition of immune tolerance, and relative thyroid hormone deficiency. Interestingly, in the current literature, better outcomes of assisted reproductive technology in women with TAI have been reported compared with earlier publications. One plausible explanation is the more widespread use of the intracytoplasmic sperm injection method. The results of randomized clinical trials have shown that levothyroxine supplementation is ineffective in preventing adverse pregnancy outcomes in women with TAI, and future research should probably be directed toward immunotherapy.